Cutaneous Metastases from Salivary Duct Carcinoma of the Submandibular Gland - Wahida Chakari; Luise Andersen; Jørgen Lock Andersen (Karger Publishers, 2017)
Salivary duct carcinoma is a rare and highly aggressive malignant neoplasm that frequently metastasises to other organs, but cutaneous metastasis is uncommon. There are only 6 cases reported in the literature with metastases to the skin and in all cases the tumour originates from the parotid gland. We present a case of skin metastases from the submandibular gland that was mistaken for basal cell carcinoma. To the best of our knowledge, this is the first reported case of salivary duct carcinoma arising from the submandibular gland with cutaneous metastases.